2014
DOI: 10.1128/aem.02666-14
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ralstonia eutropha's Poly(3-Hydroxybutyrate) (PHB) Depolymerases and Phasins on PHB Storage in Recombinant Escherichia coli

Abstract: bThe model organism for polyhydroxybutyrate (PHB) biosynthesis, Ralstonia eutropha H16, possesses multiple isoenzymes of granules coating phasins as well as of PHB depolymerases, which degrade accumulated PHB under conditions of carbon limitation. In this study, recombinant Escherichia coli BL21(DE3) strains were used to study the impact of selected PHB depolymerases of R. eutropha H16 on the growth behavior and on the amount of accumulated PHB in the absence or presence of phasins. For this purpose, 20 recomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…). In other studies, the lack of depolymerase system have found to be contributed to higher yields of PHAs (Eggers and Steinbuchel ), suggesting that phaZ can be a significant target for recombinant strains for PHA production. Engineered strains in attempts to broaden the substrate spectrum have also been manipulated (Liu et al .…”
Section: The Optimized Strategies Used In the Production Of Phasmentioning
confidence: 89%
See 1 more Smart Citation
“…). In other studies, the lack of depolymerase system have found to be contributed to higher yields of PHAs (Eggers and Steinbuchel ), suggesting that phaZ can be a significant target for recombinant strains for PHA production. Engineered strains in attempts to broaden the substrate spectrum have also been manipulated (Liu et al .…”
Section: The Optimized Strategies Used In the Production Of Phasmentioning
confidence: 89%
“…For instance, the engineered Halomonas strains could overexpress the cell division inhibitor MinCD, which not only enhance PHB accumulation but also simplify the downstream processing, resulting in a decline of the production cost (Tan et al 2014). In other studies, the lack of depolymerase system have found to be contributed to higher yields of PHAs (Eggers and Steinbuchel 2014), suggesting that phaZ can be a significant target for recombinant strains for PHA production. Engineered strains in attempts to broaden the substrate spectrum have also been manipulated (Liu et al 2014a).…”
Section: Supplying Renewable Carbon Substratesmentioning
confidence: 99%
“…Studies of PhaP2 Reu and PhaP4 Reu on PHB degradation conclude that both phasins, limit PHB degradation by interacting with the depolymerases PhaZ2, PhaZ3 and PhaZ7. Moreover, the expression of PhaP1 Reu reduced the PHB content in E. coli when expressing the phaCAB operon of R. eutropha (Eggers and Steinbüchel 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a blast search against the genome of R. eutropha strain H16 revealed that PhaZ3 shares a homology to PhaZ7 of H16 (E-value = 5e–16). It was demonstrated that induction of phaZ7 in a recombinant E. coli strain greatly reduced PHB accumulation [ 41 ]. Therefore, PhaZ3 may play an important role in PHB degradation in B. diazoefficiens .…”
Section: Discussionmentioning
confidence: 99%